Fidelidade à área e padrão de associação em Sotalia guianensis, baseado na técnica de foto-identificação - Ananias, Sandra Mara de Araújo (2006)
The behavioral patterns follow to environmental changes, including area fidelity and individuals association patterns. Several techniques are used to record these behavioral patterns and the photo-identification has been suggested as a proper tool because of its various advantages. Based on this technique, this research verified, between August of 2005 and January of 2006, area fidelity and association patterns of Sotalia guianensis, at Distrito de Pipa s bays, Rio Grande do Norte State south coast. Besides, we measured the association patterns by using the Jaccard index or Half-Weight Index (HWI). According the observation, 22 individuals were not resighted, 11 were resighted, and 36 new individuals were recorded. Nowadays, 69 individuals are cataloged. The residency rate indicated heterogeneity on studied area permanence and the association patterns between photo-identified seem to be context-specific. In addiction, the comparison of associations between two different age classes showed some individuals more frequently interacting with immature individuals. We also observed fluidity on association patterns among our individuals. We suggest that S. guianensis population from Pipa shows plasticity